Exploring neuro-inclusive design in education accommodating neurodivergent and Neurotypical Learners through sensory-generative architecture - Lazaro, Althea Clarabelle M.; Sicam, Olivia Alma G. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
In general schools in the Philippines, students with autism spectrum disorder (ASD) and
attention-deficit/hyperactivity disorder (ADHD) are becoming more prevalent. Despite their
unique challenges, scholars claim that these individuals have the potential to thrive in the
general education setting and argue for their proper accommodation. Although more learners
are being identified as neurodivergent, whose behaviors and traits stem from the differences in
the way that their brain functions, there is limited information on the spatial issues associated
with their conditions and the social stigma that they experience. This design project examines
how architecture can improve a general elementary school that addresses the psychosocial
needs of neurodivergent children. Specifically, this project investigates ways in which the
programming and sensory characteristics of spaces can be developed to create a safe and
friendly environment for these learners and allow them to form meaningful relationships with
their typically developing peers. Furthermore, this project provides research on the
development of sensory-friendly environments and the integration of a special education
resource base by understanding their social and behavioral challenges. This research argues
that a sensory design approach through the concept of harmonious coexistence can enable
neurodivergent children to become more independent and promote inclusion in the general
school setting. Thus, this project highlights the architectural design solutions that address the
wellbeing of neurodivergent learners and provides insight into the significance of their sensory
issues in shaping inclusive spaces to positively impact the way that they navigate the world
around them.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Autism spectrum disorders; Senses and sensation; Neurodiversity; Attention-deficit hyperactivity disorder; Architectural design -- Psychological aspects